A Prospective Study of Four Total Ankle Arthroplasty Implants by Non-Designer Investigators. (15th February 2017) - Lefrancois, Tina; Younger, Alastair; Wing, Kevin; Penner, Murray J.; Dryden, Peter; Wong, Hubert; Daniels, Timothy; Glazebrook, Mark
Abstract : Background: There are several types of prostheses available to surgeons when performing a total ankle arthroplasty (TAA). The main objective of this study was to summarize the clinical and functional outcomes of 4 TAA prostheses: the Hintegra implant (Integra LifeSciences), the Agility implant (DePuy), the Mobility implant (DePuy), and the Scandinavian Total Ankle Replacement (STAR) implant (Small Bone Innovations [SBi]). Methods: Patients were prospectively recruited. A total of 451 TAAs with a mean follow-up (and standard deviation) of 4.5 ± 2.0 years were included. Patients were assessed annually and completed self-reported outcome measures at these visits. Complications and revisions were reported at the time of incident. Mean improvements are reported by prosthesis. Linear mixed-effects models were used to obtain adjusted comparisons of scores across prostheses. Survivorship curves were generated by prosthesis and type of complication. Results: Mean improvement in the Ankle Osteoarthritis Scale (AOS) total score was less among patients with the Mobility implant (19.5; 95% confidence interval [CI], 15 to 24) than it was among patients with the Agility implant (29.1; 95% CI, 24 to 34), Hintegra implant (29.7; 95% CI, 27 to 33), and STAR implant (28.5; 95% CI, 23 to 34). Patients in the Mobility group also had less mean improvement in the AOS pain score (21.3; 95% CI, 17 to 26) compared with patients in the Hintegra (29.0; 95% CI, 26 to 32), Agility (29.8; 95% CI, 25 to 35), and STAR (29.1; 95% CI, 23 to 35) groups. The Mobility group also had less mean improvement in the AOS disability score (17.3; 95% CI, 12 to 23) compared with the Hintegra (30.4; 95% CI, 27 to 34), Agility (28.8; 95% CI, 23 to 34), and STAR (27.8; 95% CI, 21 to 34) groups. Survival results among the 4 prostheses are reported. Conclusions: This study demonstrated acceptable outcomes of 4 modern TAA prostheses. Outcome results from patient-reported scores were comparable between at least 3 of the 4 prostheses (the Hintegra, STAR, and Agility implants). The rates of complications and revisions found in this study are within the limits reported in the literature for similar prostheses and methods of reporting. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.